Severe Rotational Drift of an Impacted Mandibular Third Molar: A Case Report - Ehsan Abouei Mehrizi; Mostafa Esmaeili; Gholamreza Eslami Amirabadi; Mohammadamin Narimani (Journal of Dental Research, Dental Clinics, Dental Prospects, 2010)
hird molar eruption is an unpredictable event. Occasionally, mandibular third molars undergo angular changes in young adults. This rotational drift is of unknown etiology, is not predictable and may facilitate the eruption or may make the impaction worse. A rare case is presented with severe rotational drift of a mesioangularly impacted mandibular third molar.